Evaluasi Dampak Transformasi Digital Terhadap Manajemen Rumah Sakit: Tinjauan Sistematis Literatur - Reny Nugraheni (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Digital transformation has become a major driving force in modernizing hospital management worldwide. Emerging technologies such as artificial intelligence (AI), big data analytics, and cloud computing play a critical role in improving operational efficiency and the quality of healthcare services. This study employs a systematic literature review design to evaluate the impact of digital transformation on hospital management. This approach was chosen because it enables the identification, critical appraisal, and synthesis of findings from a range of empirical and conceptual studies relevant to digital transformation in hospitals. The review process follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) reporting guidelines. The findings indicate that the implementation of digital technologies in hospitals can enhance operational efficiency, reduce costs, and improve patient experience and satisfaction. Furthermore, digital transformation supports better decision-making through data-driven analytics and strengthens coordination across departments. However, several challenges remain, including budget constraints, limited technological competencies among staff, and resistance to organizational change. This study provides valuable insights for hospital managers and policymakers in planning and implementing more effective digital transformation strategies. Future research is recommended to explore practical solutions to these challenges and to further examine the potential of digital technologies in strengthening hospital management